Integration of Solar Energy Technology in Improving Energy Sustainability and Efficiency in the Fisheries Sector (Case Study of Rokan Hilir Regency, Riau Province) - Ari Prasetyo; Jhonni Rahman; Eddy Elfiano; Sehat Abdi Saragih; Sutan Lazrisyah (International Journal of Regional Innovation, 2023)
Improving sustainability and energy efficiency in the fisheries sector has emerged as an essential objective in addressing current environmental and economic concerns. One promising solution is the integration of solar energy technology in the fisheries sector. The purpose of the study was to analyse the potential and benefits of incorporating solar energy technology in improving sustainability and energy efficiency in the fisheries sector. This research included quantitative and qualitative analysis of the usage of solar energy technology in numerous aspects of the fisheries sector, such as fishing vessels, aquaculture, processing facilities, and related infrastructure. Data was collected from different locations with various characteristics during field research. The study found that integrating solar energy technology can lessen reliance on fossil fuels while also saving long-term operational costs. One of the potentials that can be used to encourage the growth of Rokan Hilir Regency, particularly in the field of fisheries, is the incorporation of solar energy technology. The Rokan Hilir Regency has the potential for solar energy conversion into electrical energy that can be used for a variety of purposes. The average peak power hour (Sun Peak Hour) for a year in Bangko District is 6.84 hours, with a minimum value of 6.23 hours in December and a maximum of 7.34 hours in August. The usage of integrated solar energy technology is utilised to support the activities of the fisheries sector, including catching, cultivating, or hatching, as well as fishing product processing. Obviously, the components used in each field must be adjusted to the level of electrical energy required. Several components that are used on fishing boats to facilitate fishing activities include spotlights, LED lights, fish cool boxes, and electric starters. Lighting lamps and DC water pumps can be used in the aquaculture industry. Solar energy is also used in the Fisheries Processing sector for LED lights and electric motors in shredded fish processing machines.